Durational Evidence That Tokyo Japanese Vowel Devoicing Is Not Gradient Reduction - Tanner, James; Sonderegger, Morgan; Torreira, Francisco (Frontiers in Psychology, 2019)
A central question in the Japanese high vowel devoicing literature concerns whether vowels are devoiced through a categorical process or via gradient reduction. Examining how vowel height and consonantal voicing condition phrase-internal CV duration in a corpus of spontaneous Tokyo Japanese, it was found that CVs containing high vowels are substantially shorter before voiceless consonants, whilst non-high vowels do not exhibit comparable shortening. This quantitative difference between CV durations suggests a controlled temporal compression of the CV, consistent with views that Japanese vowel devoicing is produced through a categorical process targeting high vowels preceding voiceless consonants, and supports previous observations made of elicited productions.